Money market funds intermediation, bank instability, and contagion - Marco Cipriani; Antoine Martin; Bruno M. Parigi (Federal Reserve Bank of New York, 2013)
In recent years, U.S. banks have increasingly relied on deposits from financial intermediaries, especially money market funds (MMFs), which collect funds from large institutional investors and lend them to banks. In this paper, we show that intermediation through MMFs allows investors to limit their exposure to a given bank (i.e., reap gains from diversifi cation). However, since MMFs are themselves subject to runs from their own investors, a banking system intermediated through MMFs is more unstable than one in which investors interact directly with banks. A mechanism through which instability can arise in an MMF-intermediated financial system is the release of private information on bank assets, which is aggregated by MMFs and could lead them to withdraw en masse from a bank. In addition, we show that MMF intermediation can also be a channel of contagion among banking institutions.
Keywords: G01; G21; G23; 330; Money market funds; bank runs